2014
DOI: 10.3945/jn.114.193573
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates D-Galactosamine/Lipopolysaccharide–Induced Liver Injury and Mitochondrial Dysfunction in Mice

Abstract: Curcumin, a naturally occurring antioxidant, has various beneficial effects in the treatment of human diseases. However, little information regarding the protection it provides against acute liver injury is available. The present study investigated the protective effects of curcumin against D-galactosamine (D-GalN)/lipopolysaccharide (LPS)-induced acute liver injury in mice. A total of 40 male Kunming mice were randomly assigned to 5 groups: 1) mice administered saline vehicle injection (control), 2) mice admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 48 publications
9
44
0
1
Order By: Relevance
“…showed significant detoxification, thereby reduced the leakage of SGOT, SGPT, ALP and total bilirubin from the hepatocytes indicating the inhibition of LPS induced toxicity in mice. These results are in agreement with the earlier reports of Zhanq et al 34 (2014) and Abdel et al 33 (2012). Where, intraperitoneal administration of curcumin (200 mg/kg b.w) and capsaicin (15,150 and 1500 µg/kg b.w) significantly reduced the LPS induced liver toxicity respectively.…”
Section: Discussionsupporting
confidence: 83%
“…showed significant detoxification, thereby reduced the leakage of SGOT, SGPT, ALP and total bilirubin from the hepatocytes indicating the inhibition of LPS induced toxicity in mice. These results are in agreement with the earlier reports of Zhanq et al 34 (2014) and Abdel et al 33 (2012). Where, intraperitoneal administration of curcumin (200 mg/kg b.w) and capsaicin (15,150 and 1500 µg/kg b.w) significantly reduced the LPS induced liver toxicity respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Previous study documented that silymarin possesses substantial protective effect against DNA damage and apoptosis induced by the environmental pollutant benzo (a) pyrene (Perumal et al 2012). Also, the effectiveness of vitamin E in quenching free radicals and functioning as a membrane stabilizer was also documented (Zhang et al 2014). It was shown that liver 8-OHdG levels increased significantly in rats intoxicated with CCl4 as compared to the control rats.…”
Section: Discussionmentioning
confidence: 86%
“…Fulminant hepatic failure can be caused by different agents such as alcohols, chemicals, and viruses [2][3][4]. LPS and GalN are the most common agents that cause hepatic injury [5,6]. The model was widely used to explore the pathogenesis of fulminant hepatitis and develop novel liver-protective reagents [7].…”
Section: Introductionmentioning
confidence: 99%